Secure Screw Placement in Management of Acetabular Fractures Using the Suprapectineal Quadrilateral Buttress Plate. (15th June 2017) - Egli, R. J.; Keel, M. J. B.; Cullmann, J. L.; Bastian, J. D.
Abstract : Acetabular fractures involving predominantly the anterior column associated with a disruption of the quadrilateral surface can be treated with instrumentation implementing the stabilization of the quadrilateral surface. The recently introduced suprapectineal quadrilateral buttress plate is specifically designed to prevent secondary medial subluxation of the femoral head, especially in elderly patients with reduced ability for partial weight bearing. Whereas there are guidelines available for safe screw fixation for the anterior and posterior columns, there might be a concern for intra-articular placement of screws placed through the infrapectineal part of the quadrilateral buttress plate. Within this report we analyzed retrospectively screw placement in 30 plates in postoperative CT scans using algorithms for metal artifact reduction. None of the screws of the buttress plate penetrated the hip joint. We describe the placement, length, and spatial orientation of the screws used for fracture fixation and suggest that the use of intraoperative image intensifiers with a combined inlet-obturator view of 30–45° best projects the screws and the hip joint. Preoperative knowledge of approximate screw placement and information for accurate intraoperative imaging may contribute to safe acetabular fracture fixation and may reduce operating time and limit radiation exposure to the patient and the personnel. This trial is registered with KEK-BE: 266/2014.